Computed tomography angiography for aerodigestive injuries in penetrating neck trauma: A systematic review. (28th September 2021) - Paladino, Lorenzo; Baron, Bonny J.; Shan, Gururaj; Sinert, Richard
Abstract: Objectives: Management of hemodynamically stable patients with penetrating neck trauma (PNT) has evolved in recent years with improvements in imaging technology. Computed tomography angiography (CTA) encompassing all zones of the neck has become part of the standard diagnostic algorithm for PNT patients who do not require immediate surgical intervention for vascular or aerodigestive injuries (ADI). Several studies have demonstrated favorable operating characteristics for CTA at excluding arterial injuries; however, consensus as to CTA's ability to detect ADI is lacking. We conducted a systematic review (PROSPERO registration number CRD42019133509) to answer the question Is CTA sufficient to rule out ADI in hemodynamically stable PNT patients without hard signs? Methods: Investigators independently searched PubMed, EMBASE, and Web of Science from their inception to August 2020 for the search terms "penetrating neck injuries" and "CT scan." To be included, studies required sufficient data to construct a 2×2 table of CTA for ADI. The operating characteristics of CTA for detecting ADIs are reported as sensitivity, specificity, and likelihood ratios (LRs), with 95% confidence intervals (95% CIs). Bias in our studies was quantified by QUADAS‐2. Results: Our search identified 1, 242 citations with seven studies with moderate to high risk of bias meeting our inclusion/exclusion criteria and encompassing 877 subjects with an ADI prevalence of 13.4%. CTA for ADI had sensitivity of 92% (95% CI = 85% to 97%), specificity of 88% (95% CI = 85% to 90%), positive likelihood ratio of 12.2 (95% CI = 4.6 to 32), and negative LR of 0.14 (95% CI = 0.05 to 0.37). Of the 26 identified esophageal injuries across our studies that were diagnosed by either swallow studies or surgical exploration, five (19%, 95% CI = 8.1% to 38.3%) were initially missed by CTA. Conclusion: CTA alone is not sufficient to exclude esophageal injuries in PNT. Because delayed diagnosis is associated with increased morbidity, additional diagnostic interventions should be undertaken if there is remaining concern for esophageal injury.